Implementasi Laporan Keuangan Sederhana pada UMKM Dapur Umi Ila - Siti Inayatun Sabilla; Endang Silaningsih; Indra Cahya Kusuma; Sri Harini; Didi Didi; Erni Yuningsih; Danu Suryani (Pusat Riset dan Inovasi Nasional, 2025)
According to data from the Ministry of Cooperatives and SMEs in 2024, Indonesia has more than 60 million SMEs, which are very important to its economy, contributing 60% to the national GDP. However, around 77.5% of SMEs do not keep financial records, while 22.5% have some form of financial reporting that is often inconsistent and poorly documented. Many entrepreneurs do not realize the importance of financial reports, instead focusing on business growth and sales. Lack of financial literacy leads to poor decision-making and operational transparency. Quality financial reports can facilitate access to capital and serve as an indicator of business success. Programs aimed at improving financial literacy and the importance of financial reporting have shown a positive impact on SME performance. The training program for Dapur Umi Ila SMEs in Bojongkerta aims to empower participants through education on financial management, emphasizing the importance of maintaining accurate financial records for proper decision-making and sustainable business growth. By creating financial reports, Dapur Umi Ila SMEs are expected to be more concerned about operational finances so that they can learn to make decisions based on relevant and reliable financial reports..